Pricing of European Vulnerable Options under the Double Exponential Jump-diffusion Model with Stochastic Volatility and Stochastic Interest Rates - Wang, Jing (Journal of Global Economy, Business and Finance, 2025)
In this paper, the pricing formula for European vulnerable options is discussed under the framework of a double-exponential jump-diffusion model with stochastic interest rates and stochastic volatility. By utilizing the characteristic function of a multidimensional stochastic vector and the Fourier-Cosine method, among other techniques, we derive the pricing formula for European vulnerable options.